Comorbid Conditions Among Adults 50 Years and Older With Traumatic Brain Injury: Examining Associations With Demographics, Healthcare Utilization, Institutionalization, and 1-Year Outcomes. Issue 4 (July 2019) - Kumar, Raj G.; Olsen, Jennifer; Juengst, Shannon B.; Dams-O'Connor, Kristen; O'Neil-Pirozzi, Therese M.; Hammond, Flora M.; Wagner, Amy K.
Abstract : Objectives: To assess the relationship of acute complications, preexisting chronic diseases, and substance abuse with clinical and functional outcomes among adults 50 years and older with moderate-to-severe traumatic brain injury (TBI). Design: Prospective cohort study. Participants: Adults 50 years and older with moderate-to-severe TBI ( n = 2134). Measures: Clusters of comorbid health conditions empirically derived from non-injury International Classification of Diseases, Ninth Revision codes, demographic/injury variables, and outcome (acute and rehabilitation length of stay [LOS], Functional Independence Measure efficiency, posttraumatic amnesia [PTA] duration, institutionalization, rehospitalization, and Glasgow Outcome Scale–Extended (GOS-E) at 1 year). Results: Individuals with greater acute hospital complication burden were more often middle-aged men, injured in motor vehicle accidents, and had longer LOS and PTA. These same individuals experienced higher rates of 1-year rehospitalization and greater odds of unfavorable GOS-E scores at 1 year. Those with greater chronic disease burden were more likely to be rehospitalized at 1 year. Individuals with more substance abuse burden were most often younger (eg, middle adulthood), black race, less educated, injured via motor vehicle accidents, and had an increased risk for institutionalization. Conclusion: Preexisting health conditions and acute complications contribute to TBI outcomes. This work provides a foundation to explore effects of comorbidity prevention and management on TBI recovery in older adults.